Central Banks in European Emerging Market Economies in the 1990s - Eduard Hochreiter; Tadeusz Kowalski (Oesterreichische Nationalbank (OeNB), 2000)
This paper analyzes the institutional framework of central banks in ten Central and East European countries using the ECB as benchmark. It looks at the legislated objectives of these central banks, assesses the degree of political and functional independence and the status of their democratic legitimization and accountability. We find that while much progress has been made in making the statutes "Maastricht compatible", all of them will have to be adapted once again before EMU entry. The legislation provides for democratic accountability comparable to that of the ESCB. In recent years the enacted limitations of fiscal financing have become more binding. Rescue operations in the financial sector might be seen as encroaching the independence of the central bank.
Keywords: E52; E58; 330; central bank independence; central bank accountability; emerging market economies